2014
DOI: 10.1021/am4058887
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Hydrogen Separation in Porous Graphene Membrane: First-Principle and Molecular Dynamic Simulation

Abstract: First-principle density functional theory (DFT) calculation and molecular dynamic (MD) simulation are employed to investigate the hydrogen purification performance of two-dimensional porous graphene material (PG-ESX). First, the pore size of PG-ES1 (3.2775 Å) is expected to show high selectivity of H2 by DFT calculation. Then MD simulations demonstrate the hydrogen purification process of the PG-ESX membrane. The results indicate that the selectivity of H2 over several other gas molecules that often accompany … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(127 citation statements)
references
References 61 publications
4
123
0
Order By: Relevance
“…Furthermore, strong improvements in the permeance of water, 45 water vapor and oxygen were achieved, as compared to current state- 46 of-the-art membranes [18]. However, the preparation of well-defined 47 pores for very high separation ratios is still challenging, as it requires 48 manipulation of graphene on an atomic scale and sometimes special 49 edge termination [12,19]. 50 Several groups investigated the properties of graphene as mem-51 brane for gas containment, and for corrosion inhibition with various 52 techniques; one example is a micro chamber etched into a SiO 2 53 substrate sealed with transferred graphene that was investigated with 54 atomic force microscopy (AFM) [9].…”
mentioning
confidence: 99%
“…Furthermore, strong improvements in the permeance of water, 45 water vapor and oxygen were achieved, as compared to current state- 46 of-the-art membranes [18]. However, the preparation of well-defined 47 pores for very high separation ratios is still challenging, as it requires 48 manipulation of graphene on an atomic scale and sometimes special 49 edge termination [12,19]. 50 Several groups investigated the properties of graphene as mem-51 brane for gas containment, and for corrosion inhibition with various 52 techniques; one example is a micro chamber etched into a SiO 2 53 substrate sealed with transferred graphene that was investigated with 54 atomic force microscopy (AFM) [9].…”
mentioning
confidence: 99%
“…All molecular dynamic simulations were performed in an NVT enable to gases [7]. However, several studies have suggested that graphene has the potential to induce highly selective transport by generation of pore defects [8][9][10][11][12][13][14], in which atoms can be removed from the graphene lattice to create pores of specific size and geometry.…”
Section: Simulation Details and Methodsmentioning
confidence: 99%
“…Over the past five years, many computational studies have suggested that porous graphene-based membranes with desirable pore geometry could achieve an excellent permeance and selectivity [75,[91][92][93] [84]. In this study, the micrometer-scale membranes with sub-nanometer-sized pores were created via ultraviolet oxidative etching method, and the gas leak experiments indicated that the gas molecules with the kinetic diameter smaller than 3.4 Å were much more permeable than those with the kinetic diameter larger than 3.4 Å. Consequently, the H 2 /CO 2 ideal selectivity was about 1.7, which was likely due to the larger pore size than CO 2 and H 2 molecules.…”
Section: Carbon-based Membranesmentioning
confidence: 99%